2011
DOI: 10.1038/srep00046
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule sensing electrode embedded in-plane nanopore

Abstract: Electrode-embedded nanopore is considered as a promising device structure for label-free single-molecule sequencing, the principle of which is based on nucleotide identification via transverse electron tunnelling current flowing through a DNA translocating through the pore. Yet, fabrication of a molecular-scale electrode-nanopore detector has been a formidable task that requires atomic-level alignment of a few nanometer sized pore and an electrode gap. Here, we report single-molecule detection using a nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
89
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 32 publications
0
89
0
Order By: Relevance
“…While these theoretical results on simple model systems were promising, no experimental studies on graphene nanogaps for DNA sequencing were reported so far, likely because of the significant experimental challenges involved (creating and maintaining a few-nm gap between graphene electrodes, slowly traversing DNA through it in a controlled way, and performing tunneling current measurements while base, water, and ion fluctuations yield significant tunneling current noise). Results on metallic tunneling electrodes embedded in silicon nitride nanopores [56,57] are encouraging, however, and similar experiments using graphene electrodes are to be expected.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…While these theoretical results on simple model systems were promising, no experimental studies on graphene nanogaps for DNA sequencing were reported so far, likely because of the significant experimental challenges involved (creating and maintaining a few-nm gap between graphene electrodes, slowly traversing DNA through it in a controlled way, and performing tunneling current measurements while base, water, and ion fluctuations yield significant tunneling current noise). Results on metallic tunneling electrodes embedded in silicon nitride nanopores [56,57] are encouraging, however, and similar experiments using graphene electrodes are to be expected.…”
Section: Discussionmentioning
confidence: 55%
“…The idea of this 'recognition tunneling' originates from successful experiments performed to slow down DNA while it moves through a gap [52][53][54]. Much efforts were focussed on measuring DNA with metallic tunneling electrodes embedded in silicon nitride pores [52,[55][56][57][58][59], and indeed, some sequence information could be extracted when the DNA was pulled through the gap by an electric field [56,57].…”
Section: Tunneling Across a Graphene Nanogapmentioning
confidence: 99%
“…Additional methods have been proposed, including local heating of a gold layer surrounding the nanopore to stretch the DNA [65,66] and ratcheting of nucleotide strands through introduction of a third electrode [67,68]. In fact, researchers have investigated a three-terminal system, or field effect nanofluidic transistor, which would alter the electric field profile in the nanopore [69][70][71] and modulate its surface charge [72][73][74][75]. Base-by-base ratcheting using electrostatic traps in a DNA transistor has yet to be achieved, but nanopore modifications have already reduced translocation speeds by up to an order of magnitude for ssDNA [62,73].…”
Section: Introductionmentioning
confidence: 99%
“…Although the size of the pore can be tuned 11 and the devices can be integrated with other single-molecule techniques 9,10,12 and detection mechanisms [13][14][15][16] , they have yet to deliver sequencing data. One reason for this is that the nanopores are typically fabricated in SiN x or SiO 2 membranes, which have thicknesses that are large compared to the size of a DNA base.…”
mentioning
confidence: 99%